The Effects of Transformational Leadership on Job Contentment - Loc , Nguyen Duc; Loc , Nguyen Duc; Minh, Ngo Ngoc (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to analyze the influence of transformational leadership on job contentment among teachers. This study used the modified transformational leadership measurement tool. Meanwhile, Teachers Job Contentment was adopted and adapted form job contentment questionnaire. Data collected from 400 respondents in Hochiminh City-Vietnam. Data based were analyzed using the Partial Least Squares software through the SMART PLS 3.0 software. The findings showed that there is significant influence between the dimensions of charismatic, consideration and motivation inspiration, and intellectual stimulation on job contentment. These findings can be used as a direction to the Ministry of Education to empower all the strengths and weaknesses in the educational management field.